Parental knowledge, awareness, and attitudes towards children’s oral habits: a descriptive cross-sectional study - Sarah Almugairin; Alanoud Alwably; Nada Alayed; Alanoud Algazlan; Hadeel Alrowaily; Elzahraa Eldwakhly; Abdullazez Almudhi (Acta Odontologica Scandinavica)
Background: Oral health is fundamental to children’s health and well-being. Parental knowledge, awareness, and practices towards oral habits significantly influence children’s oral health. Early diagnosis and intervention to break abnormal oral habits are vital to prevent long-term detrimental effects on oral and facial development. Objective: This study aimed to assess parents’ knowledge, awareness, and attitudes towards their children’s oral habits in Riyadh, Saudi Arabia. Methods: A cross-sectional study design was employed, where 2,000 participants were enrolled, of whom 563 Saudi mothers residing in Riyadh met the inclusion criteria. A validated, self-administered questionnaire was used to collect data on demographics, child information, parental awareness, and parental attitudes.